1990
DOI: 10.2214/ajr.154.1.2104734
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of bowel infarction: a comparison of plain films and CT scans in 23 cases.

Abstract: We retrospectively reviewed abdominal CT and plain film findings in 23 proved cases of mesenteric infarction to compare the value of the two techniques. Criteria considered specific for infarction on CT were identified in nine (39%) of 23 patients and comprised pneumatosis in seven patients (30%), mesenteric or portal venous gas in three patients (13%), and focally thick-walled bowel in two patients (9%). Criteria considered specific for bowel infarction on plain films were identified in seven (30%) of 23 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
9

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(48 citation statements)
references
References 7 publications
2
37
0
9
Order By: Relevance
“…Direct radiography and abdominal ultrasonography are non-diagnostic and abdominal computed tomography has a low sensitivity and specificity (9,10). Although mesenteric vessels are visualized with an abdominal MRI, studieson the reliability of the results are limited.…”
mentioning
confidence: 99%
“…Direct radiography and abdominal ultrasonography are non-diagnostic and abdominal computed tomography has a low sensitivity and specificity (9,10). Although mesenteric vessels are visualized with an abdominal MRI, studieson the reliability of the results are limited.…”
mentioning
confidence: 99%
“…These finding were similar to the findings of the study done by others in which they had reported approximately 50% patients had no significant X ray abdomen findings. 18,19 In the patients of bowel ischemia group smoking was associated with 56% of cases, 48% patients were found to be alcoholic. 28% patients were diabetic and 16% patients had history of cardiac disease in our study similar to the findings of previous studies which reported that among patients who had bowel ischemia smoking, alcoholism and diabetes were associated with 60%, 40% and 17% of patients respectively and 20% had past cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Special laboratory tests, like serum alpha-glutathione S-transferase and intestinal fatty acid binding protein-I (I-FABP) are under evaluation [31,32]. An abdominal radiograph in AMI is also nonspecific as normal findings may be present in 25% of cases [33][34][35]. Characteristic radiographic abnormalities, such as thumbprinting or thickening of bowel loops, occur in less than 40% of patients at presentation.…”
Section: Diagnosismentioning
confidence: 99%
“…Characteristic radiographic abnormalities, such as thumbprinting or thickening of bowel loops, occur in less than 40% of patients at presentation. Presence of air in the portal vein is also a late finding associated with a grave prognosis [34]. The utility of a plain abdominal radiography helps to exclude other acute abdominal pathologies, such as intestinal obstruction or a perforated hollow viscus.…”
Section: Diagnosismentioning
confidence: 99%